2020
DOI: 10.1038/s41598-020-70915-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental prospecting of black yeast-like agents of human disease using culture-independent methodology

Abstract: Melanized fungi and black yeasts in the family Herpotrichiellaceae (order chaetothyriales) are important agents of human and animal infectious diseases such as chromoblastomycosis and phaeohyphomycosis. the oligotrophic nature of these fungi enables them to survive in adverse environments where common saprobes are absent. Due to their slow growth, they lose competition with common saprobes, and therefore isolation studies yielded low frequencies of clinically relevant species in environmental habitats from whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…However, some groups have remained unexplored by conventional culture‐based methods. Our study systematically investigated in silico the presence of the Chaetothyriales sequences in metagenomic public datasets, using sequences of validated molecular markers following the methodologies proposed by Costa et al 25 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some groups have remained unexplored by conventional culture‐based methods. Our study systematically investigated in silico the presence of the Chaetothyriales sequences in metagenomic public datasets, using sequences of validated molecular markers following the methodologies proposed by Costa et al 25 …”
Section: Discussionmentioning
confidence: 99%
“…Chromoblastomycosis is a chronic, granulomatous mycosis of skin and subcutaneous tissue caused by the implantation of contaminated plant spines or wood fragments 19,21–23 . Epidemiological studies found that mycosis has an environmental origin 23–25 . Phaeohyphomycosis is a general term used to refer to opportunistic, cutaneous and systemic infections caused by melanized fungi involving immunocompromised and healthy individuals 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many species of melanised filamentous fungi and black yeasts that belong to the Herpotrichiellaceae family are agents involved in subcutaneous, systemic or disseminated infections, known as chromoblastomycosis (CBM) or phaeohyphomycosis (PHM). 1 , 2 , 3 , 4 Some species of this family also cause eumycotic mycetoma. 5 …”
mentioning
confidence: 99%
“…Many species of melanised filamentous fungi and black yeasts that belong to the Herpotrichiellaceae family are agents involved in subcutaneous, systemic or disseminated infections, known as chromoblastomycosis (CBM) or phaeohyphomycosis (PHM). (1,2,3,4) Some species of this family also cause eumycotic mycetoma. (5) CBM is an implantation neglected disease, caused by melanised fungi widely found in nature which infect mainly agricultural workers after transcutaneous inoculation, (2,6,7,8) thus constituting an occupational disease.…”
mentioning
confidence: 99%